Profile of children admitted with seizures to a tertiary care rural hospital in Mandya district - Dr Shivaprakash NC; Dr Touseef Ahmed; Dr Ravichandra Rao (Pediatric Review: International Journal of Pediatric Research, 2015)
Background: Seizures is one of the common causes of pediatric admissions to hospitals with significant mortality and morbidity. As there is limited data on profile regarding acute seizures episodes form the developing countries this study was undertaken. This study aims to assess the age wise distribution, etiology of seizure, classify seizure types and the outcome in children presenting with seizures to our hospital. Methods: This is a hospital based prospective study carried out in the Department of Pediatrics, Adichunchanagiri Institute of Medical Sciences, B.G Nagara, Mandya from 1st June 2014 to 31st May 2015. Parameters such as demographics, clinical presentations, laboratory tests, neuroimaging studies, EEG, diagnosis and course in hospital were assessed. Results: A total of 118 patients were admitted with seizures of which 69 (58.47%) were males and 49 (41.52%) females. Among these patients, 90 (76.27%) presented with fever and 105 (88.99%) children were less than 6 years of age. Generalized seizures were the most common seizure type 81(68.64%). Febrile seizures 57 (48.30%), symptomatic seizures 19(16.1%), seizure disorder 16 (13.55%), and seizures in cerebral palsy 8 (6.8%) were common etiologies. Conclusions: Acute episode of seizures are one of the commonest cause of hospitalization with high mortality. Febrile convulsions and CNS infections were common causes of seizures in febrile children. Seizures were more common in age 1month to 1year. Neuroimaging should be advised in all afebrile children and in children with partial seizures. CNS infections like meningitis and encephalitis, neurocysticercosis can be prevented with improvement in health care facilities.